Nighttime Magnetic Perturbation Events Observed in Arctic Canada: 3. Occurrence and Amplitude as Functions of Magnetic Latitude, Local Time, and Magnetic Disturbance Indices. Issue 3 (18th March 2021) - Engebretson, Mark J.; Pilipenko, Viacheslav A.; Steinmetz, Erik S.; Moldwin, Mark B.; Connors, Martin G.; Boteler, David H.; Singer, Howard J.; Opgenoorth, Hermann; Schillings, Audrey; Ohtani, Shin; Gjerloev, Jesper; Russell, Christopher T.
Abstract: Rapid changes of magnetic fields associated with nighttime magnetic perturbation events (MPEs) with amplitudes |Δ B | of hundreds of nT and 5–10 min duration can induce geomagnetically induced currents (GICs) that can harm technological systems. This study compares the occurrence and amplitude of nighttime MPEs with |d B /d t | ≥ 6 nT/s observed during 2015 and 2017 at five stations in Arctic Canada ranging from 64.7° to 75.2° in corrected geomagnetic latitude (MLAT) as functions of magnetic local time (MLT), the SME (SuperMAG version of AE) and SYM/H magnetic indices, and time delay after substorm onsets. Although most MPEs occurred within 30 min after a substorm onset, ∼10% of those observed at the four lower latitude stations occurred over two hours after the most recent onset. A broad distribution in local time appeared at all five stations between 1700 and 0100 MLT, and a narrower distribution appeared at the lower latitude stations between 0200 and 0700 MLT. There was little or no correlation between MPE amplitude and the SYM/H index; most MPEs at all stations occurred for SYM/H values between −40 and 0 nT. SME index values for MPEs observed >1 h after the most recent substorm onset fell in the lower half of the range of SME values for events during substorms, and dipolarizations in synchronous orbit at GOES 13 during these events were weaker or more often nonexistent. These observations suggest that substorms are neither necessary nor sufficient to cause MPEs, and hence predictions of GICs cannot focus solely on substorms. Key Points: We present 2 years of observations of ≥6 nT/s magnetic perturbation events (MPEs) from five high‐latitude Arctic stations Most MPEs occurred within 30 min of a substorm onset, but substorms were neither necessary nor sufficient to cause MPEs Pre‐ and postmidnight MPEs had different temporal relations to substorms and occurred at slightly different latitudes